2019
DOI: 10.1103/physrevc.99.045206
|View full text |Cite
|
Sign up to set email alerts
|

Tetraquarks with hidden charm and strangeness as ϕψ(2S) hadrocharmonium

Abstract: In the hadrocharmonium picture acc state and a light hadron form a bound state. The effective interaction is described in terms of the chromoelectric polarizability of thecc state and energymomentum-tensor densities of the light hadron. This picture is justified in the heavy quark limit, and may successfully account for a hidden-charm pentaquark state recently observed by LHCb. In this work we extend the formalism to the description of hidden-charm tetraquarks, and address the question of whether the resonant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Hadro-quarkonia are heavy-light tetra-or pentaquark configurations, where a compact Q Q state (with Q = c or b), labelled as ψ in the following, is embedded in light hadronic matter, H = qqq or q q (where q = u, d or s) [12,[45][46][47][48][49][50][51][52][53][54][55]. The heavy and light constituents, ψ and H, develop an attractive force, which is the result of multiple-gluon exchange between them.…”
Section: Hadro-quarkonium Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Hadro-quarkonia are heavy-light tetra-or pentaquark configurations, where a compact Q Q state (with Q = c or b), labelled as ψ in the following, is embedded in light hadronic matter, H = qqq or q q (where q = u, d or s) [12,[45][46][47][48][49][50][51][52][53][54][55]. The heavy and light constituents, ψ and H, develop an attractive force, which is the result of multiple-gluon exchange between them.…”
Section: Hadro-quarkonium Modelmentioning
confidence: 99%
“…Therefore, hidden-charm and bottom tetraquark states with non-null strangeness content cannot take place neither in the UQM [13][14][15][16][17][18][19][20][21][22][23] nor in the molecular model [24][25][26][27][28][29] interpretations. On the contrary, these exotic configurations are expected (if above threshold) both in the compact tetraquark [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and hadro-quarkonium [12,[45][46][47][48][49][50][51][52][53][54][55] models. See Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in Ref. [100] the authors suggested to assign the X (4274) to a ψ(2S)φ S-wave hadrocharmonium configuration.…”
Section: (4274): Other Interpretationsmentioning
confidence: 99%
“…However, the J/ψ − φ potential was found too weak, in lattice QCD, to form a bound states [7]. Furthermore, the Ψ(2S) − φ bound state has already been assigned to X(4274) [8] so that rules out the possibility that X(4700) be a s-wave Ψ(2S) − φ bound state. Anyway, X(4700) could be other hadrocharmonium states in specific regions of the parameter space.…”
Section: *mentioning
confidence: 99%